On production ultrashort- and short-lived isotopes for nuclear medicine at cyclotron CV-28 - Petrusenko, Yu.T.; Nikolaichuk, L.I.; Tutubalin, A.I.; Shepelev, A.G.; Ponomarenko, T.A.; Nemashkalo, O.V. (Вопросы атомной науки и техники, 2009)
The paper presents a survey of experimental methods for cyclotron production of ultrashort-lived (USL) and short-lived (SL) radionuclides recommended by the IAEA as most widely used in nuclear medicine. The data on radionuclide-producing nuclear reactions, the required energy range and targets are given. The undertaken analysis of experimental studies carried out at different scientific centers as well as the comparison with the parameters of the cyclotron CV-28 to be put into operation at the NSC KIPT suggest the conclusion about the operational capabilities of the isochronous cyclotron CV-28 to produce the mentioned radionuclides and the possibility of creating the positron-emission tomography (PET) with the CV-28 as the base.